Knowledge and practices on food safety among secondary school students in Johor Bahru, Johor, Malaysia - Norazmir, M.N.; Noor Hasyimah, M.A.; Siti Shafurah, A.; Siti Sabariah, B.; Ajau, D.; Hazali, Norazlanshah (Asian Network for Scientific Information, 2012)
The issue of food safety is an issue that is discussed widely, but cases of food poisoning in particular, are still continuing. This may be associated with their own level of knowledge and practices on food safety. This study was aimed to examine the level of food safety knowledge and practices from two secondary school students, to investigate the association between food safety knowledge and practices with gender, to identify the correlation between food safety knowledge levels with practices and to compare the difference of knowledge and practices level between both of the school. Information concerning demographic, food safety knowledge and practices were collected using self administered questionnaire. 339 students comprising 202 male and 197 female from two schools were randomly selected to answer the questionnaire provided. Analyzed data obtained stated that knowledge on food safety was good for both school and their also practiced on food safety by 79.1% included in good practice range. Results also showed that a high level of food safety knowledge and practices was possessed by both groups, male and female students in quite similar value of means. Correlation between food safety knowledge and practices on food safety indicated, there was a small positive correlation with [r = 0.148, n = 221, p<0.05] for Sekolah Tinggi Arab Maahad and [r = 0.053, n = 178, p<0.5] for Sekolah Menengah Kebangsaan Gelang Patah.